2010
DOI: 10.1007/s10620-010-1384-1
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Administration of Lactobacillus casei DG Modifies Flora Composition and Toll-Like Receptor Expression in Colonic Mucosa of Patients with Mild Ulcerative Colitis

Abstract: Manipulation of mucosal microbiota by L. casei DG and its effects on the mucosal immune system seem to be required to mediate the beneficial activities of probiotics in UC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 47 publications
(64 reference statements)
1
42
0
Order By: Relevance
“…TLRs first recognize the pathogen associated molecular patterns (PAMPs) and trigger a series of cascades to activate nuclear factor-κB and mitogen activated protein kinase P38, which subsequently induce the release of various cytokines, including IL-6, IL-1, IL-8, IL-10, IL-12, TNF-α, nitric oxide synthase, and B7 molecules. Thus, TLRs aggravate inflammatory reactions (23,24). Haller et al (25) has reported that peptidoglycans and lipopolysaccharides of bacteria may act as PAMPs to interact with TLR2 and TLR4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs first recognize the pathogen associated molecular patterns (PAMPs) and trigger a series of cascades to activate nuclear factor-κB and mitogen activated protein kinase P38, which subsequently induce the release of various cytokines, including IL-6, IL-1, IL-8, IL-10, IL-12, TNF-α, nitric oxide synthase, and B7 molecules. Thus, TLRs aggravate inflammatory reactions (23,24). Haller et al (25) has reported that peptidoglycans and lipopolysaccharides of bacteria may act as PAMPs to interact with TLR2 and TLR4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this approach remarkably reduced the levels of TLR-4 and IL-1β mRNA while increasing mucosal IL-10. Accordingly, modification of mucosal microbiota by L. casei DG and its impacts on the mucosal immunity seem to be critical for the favorable roles of this probiotics in ulcerative colitis patients [128]. …”
Section: Reviewmentioning
confidence: 99%
“…d'incà et al (ref. 37 ) evaluated the effect of an 8-week oral and/or rectal administration of lactobacillus casei dG on colonic-associated microbiota, mucosal cytokine balance, and Tlr expression in patients with mild left-sided Uc. The patients were divided into three groups: the first group received oral 5-asa alone, the second group received oral 5-asa plus oral lactobacillus casei dG (8 × 108 cFU), and the third group received oral 5-asa and rectal lactobacillus casei dG (8 × 108 cFU).…”
Section: Discussionmentioning
confidence: 99%